What are the benefits and harms of ureteroscopy compared with shock-wave lithotripsy in the treatment of upper ureteral stones?: a systematic review - Drake, Tamsin; Knoll, Thomas (European urology, 2017)
Context: Extracorporeal shock wave lithotripsy (SWL) and ureteroscopy (URS), with or without intracorporeal lithotripsy, are the most common treatments for upper ureteric stones. With advances in technology, it is unclear which treatment is most effective and/or safest. Objective: To systematically review literature reporting benefits and harms of SWL and URS in the management of upper ureteric stones. Evidence acquisition: Databases including Medline, Embase, and the Cochrane library were searched from January 2000 to November 2014. All randomised controlled trials (RCTs), quasi-randomised controlled trials, and nonrandomised studies comparing any subtype or variation of URS and SWL were included. The primary benefit outcome was stone-free rate (SFR). The primary harm outcome was complications. Secondary outcomes included retreatment rate, need for secondary, and/or adjunctive procedures. The Cochrane risk of bias tool was used to assess RCTs, and an extended version was used to assess nonrandomised studies. Grading of Recommendations Assessment, Development, and Evaluation was used to assess the quality of evidence. Evidence synthesis: Five thousand-three hundred and eighty abstracts and 387 full-text articles were screened. Forty-seven studies met inclusion criteria; 19 (39.6%) were RCTs. No studies on children met inclusion criteria. URS and SWL were compared in 22 studies (4 RCTs, 1 quasi-randomised controlled trial, and 17 nonrandomised studies). Meta-analyses were inappropriate due to data heterogeneity. SFR favoured URS in 9/22 studies. Retreatment rates were higher for SWL compared with URS in all studies but one. Longer hospital stay and adjunctive procedures (most commonly the insertion of a JJ stent) were more common when primary treatment was URS. Complications were reported in 11 out of 22 studies. In eight studies, it was possible to report this as a Clavien-Dindo Grade. Higher complication rates across all grades were reported for URS compared with SWL. For intragroup (intra-SWL and intra-URS) comparative studies, 25 met the inclusion criteria. These studies varied greatly in outcomes measured with data being heterogeneous. Conclusions: Compared with SWL, URS was associated with a significantly greater SFR up to 4 wk but the difference was not significant at 3 mo in the included studies. URS was associated with fewer retreatments and need for secondary procedures, but with a higher need for adjunctive procedures, greater complication rates, and longer hospital stay. Patient summary: In this paper, the relative benefits and harms of the two most commonly offered treatment options for urinary stones located in the upper ureter were reviewed. We found that both treatments are safe and effective options that should be offered based on individual patient circumstances and preferences.
Gesehen am 18.10.2018
Available online 26 April 2017